Optimalisasi Peningkatan Kunjungan Posyandu Lansia di Puskesmas Kerinci Kanan Kabupaten Siak - Dea Sari; Ahmad Satria Efendi; Handry Handry (Jurnal Ners, 2026)
The growing elderly population and their complex health needs require optimized elderly integrated health post services as key promotive and preventive efforts at the primary care level. In Kerinci Kanan Health Center, Siak Regency, elderly attendance at the posyandu remains low, resulting in inadequate health monitoring. This residency aimed to analyze contributing factors and develop effective intervention strategies. A qualitative case study design was applied from October 13–30, 2025. Participants were selected purposively, including the Head of the Health Center, elderly program officers, health cadres, and older adults. Data were obtained through direct observation, in-depth interviews, and review of program reports. Data validity was ensured through source and method triangulation and member checking. Analysis employed the USG method to determine priority problems and fishbone analysis to explore root causes, supported by thematic analysis. Findings revealed that low attendance was influenced by limited elderly knowledge, lack of family support, accessibility barriers, inadequate human resources and facilities, and suboptimal health education and cadre empowerment. Recommended interventions included strengthening health education, improving cadre capacity, enhancing service flow, and reinforcing multisectoral collaboration. In conclusion, optimizing elderly posyandu attendance requires a comprehensive and context-specific approach focusing on education, accessibility, service quality, and cadre involvement